2022
DOI: 10.3390/ma15051704
|View full text |Cite
|
Sign up to set email alerts
|

The Seismic Performance of New Self-Centering Beam-Column Joints of Conventional Island Main Buildings in Nuclear Power Plants

Abstract: In order to improve the deformation energy consumption and self-centering ability of reinforced concrete (RC) frame beam-column joints for main buildings of conventional islands in nuclear power plants, a new type of self-centering joint equipped with super-elastic shape memory alloy (SMA) bars and a steel plate as kernel components in the core area of the joint is proposed in this study. Four 1/5-scale frame joints were designed and manufactured, including two contrast joints (a normal reinforced concrete joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Therefore, superelastic SMA can be used in seismic structures to improve the energy dissipation capacity and provide self-centering capacity for structures. Pei et al [ 23 ] found that SMA bars were able to improve the bearing capacity, ductility, and self-centering capability of concrete beam–column joints. Cortés-Puentes et al [ 24 ] proved that the shear walls strengthened by SMA rods had a self-centering ability and were able to self-repair the damaged areas.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, superelastic SMA can be used in seismic structures to improve the energy dissipation capacity and provide self-centering capacity for structures. Pei et al [ 23 ] found that SMA bars were able to improve the bearing capacity, ductility, and self-centering capability of concrete beam–column joints. Cortés-Puentes et al [ 24 ] proved that the shear walls strengthened by SMA rods had a self-centering ability and were able to self-repair the damaged areas.…”
Section: Introductionmentioning
confidence: 99%
“…established the discrete element model of connecting aisle excavation of the same size, and studied the surface settlement during shield excavation and the particle coordination number in the soil before the excavation. Many other scholars have also done a lot of work in the field of construction technology and risks of connecting aisle (Pei and Tao, 2011;Pei et al, 2013;Han et al, 2015;Li et al, 2015;Li et al, 2019;Wang et al, 2020a;Wang et al, 2020b;Wu et al, 2020;Yuan et al, 2020;Zhang and Zhong, 2020;Yuan et al, 2021a;Yuan et al, 2021b;Dai and Hu, 2021;Du et al, 2021;Ting et al, 2021;Wang and Meng, 2021;Zhang et al, 2021;Yuan et al, 2022a;Yuan et al, 2022b;Yuan et al, 2022c;Kun et al, 2022;Liu et al, 2022;Pei et al, 2022;Wang et al, 2022;Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed approach was validated by experiments. Papers [ 2 , 3 , 4 , 5 ] focus on the applications of SMAs in braces and connections in residential buildings/industrial structures. Zhang et al [ 2 ] present a novel type of hybrid self-centering braces incorporating tension-only superelastic NiTi shape memory alloy (SMA) cables and integrated viscoelastic dampers (VEDs).…”
mentioning
confidence: 99%
“…They have also developed improved numerical models combined with the Graesser and Bouc–Wen models in MATLAB. Pei et al [ 4 ] examine a new type of self-centering reinforced concrete (RC) frame beam-column joint, equipped with super-elastic SMA bars. It is shown that by using the SMA reinforcement and a steel plate, the load carrying capacity is improved, the stiffness degradation is delayed, and the ductility and self-centering ability of the joints is improved.…”
mentioning
confidence: 99%
See 1 more Smart Citation